A case of large-cell lung carcinoma successfully treated with pembrolizumab but complicated with cholangitis - Ooi, Ryunosuke (Respir Med Case Rep, 2020)
Large-cell carcinoma (LCC) of the lung is defined as an undifferentiated non-small cell lung cancer (NSCLC) and accounts for approximately 7.5% of lung cancers. Immune checkpoint inhibitors (ICIs) may be effective for LCC, but there has been no firm evidence due to its low frequency. We herein report an 80-year-old woman with LCC of the lung who was successfully treated with pembrolizumab but developed sclerosing cholangitis as an immune-related adverse event. This case highlights the efficacy of ICIs for LCC as well as the importance of the immediate and detailed management of ICI-related sclerosing cholangitis.